DAMPAK POSITIF BERORGANISASI DAN BUDAYA ORGANISASI BAGI MAHASISW DAN PEKERJA GENERASI Z - A.putri Andini; Natasyah Natasyah; Haedar Haedar (RESEARCH FAIR UNISRI, 2024)
This research aims to determine the positive impact of organizations and organizational culture on generation z students and workers. The position of the organization is quite important in aspects of life both in industry, government, social organizations, society and others. Organizations as part of the branch of social science have a fairly large role in human life. Organizational culture refers to shared assumptions. Organizations can occur if there is a group of people working together to achieve the same goal. "Organizational culture is customs, traditions, norms and general ways of doing things in an organization as a result of what has been done previously." Organizational culture that differentiates an organization from other organizations is a system of meaning shared by its members. Corporate culture is a source of sustainable competitive advantage. This research shows that organizational culture is a key element of organizational effectiveness. This research was conducted using quantitative methods, namely questionnaires. Where the population is 36 and the sample is 31 students and workers. The results of this research state that there are still many Generation Z students and workers who are interested in joining organizations and state that organizational culture has a positive impact on them. The limitations of this research are, the lack of samples that have been studied. In this research we only used 2 variables to look at organizational interest in Generation Z workers and students.